Lest We Forget: Covid-19, the Defense Production Act, and Executive Order 13,917 - N. Brock Enger (Columbia Journal of Race and Law)
During his 2024 presidential campaign, Donald Trump claimed that the ongoing conflicts in Ukraine and Gaza would not have occurred had he been reelected in 2020. However, during his first presidency, President Trump faced another significant adversary—the COVID-19 pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)—and many contend that Trump’s inadequate response to this viral enemy contributed significantly to his 2020 election loss. Central to the pandemic response was the Defense Production Act, a Cold War–era statute granting broad emergency powers.